ANALISIS STUDI KASUS DENGAN MENGGUNAKAN TEKNIK IFAS DAN EFAS - Maula, Nurkholifatul (Badan Penelitian dan Pengembangan Daerah Provinsi Jawa Barat, 2024)
The Ciwaringin handwritten batik industry still faces many obstacles, including production process challenges and long production durations which can hinder cash flow turnover, marketing issues, and the limited skills and knowledge of the artisans, making it difficult for the Ciwaringin batik industry to grow. To foster the growth of the Ciwaringin batik industry, internal and external evaluations are necessary. This research aims to analyze the challenges and future of the Ciwaringin batik industry using SWOT analysis and calculations with IFAS and EFAS matrices. The study employed a descriptive qualitative approach with Miles and Huberman's analysis techniques. The results indicate that the IFAS value (strength and weakness) is 2.92, identifying that the IFAS value is in quadrant V (Five), which represents an average score. Therefore, there is a need for improvement in the internal factors of the Ciwaringin batik industry. The EFAS value of the Ciwaringin batik industry is 2.65, which falls in the